2007
DOI: 10.4269/ajtmh.2007.77.176
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Dissemination of Venezuelan Equine Encephalitis Virus in the Epidemic Mosquito Vector, Aedes taeniorhynchus

Abstract: The mosquito Aedes taeniorhynchus is an important epidemic vector of Venezuelan equine encephalitis virus (VEEV), but detailed studies of its infection are lacking. We compared infection by an epidemic VEEV strain to that by an enzootic strain using virus titrations, immunohistochemistry, and a virus expressing the green fluorescent protein. Ae. taeniorhynchus was more susceptible to the epidemic strain, which initially infected the posterior midgut and occasionally the anterior midgut and cardia. Once dissemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…This suggests that the proliferation of ZIKV in Ae. aegypti salivary glands is not attributed to direct dissemination from the midgut, but rather a result of viral dissemination and amplification within the glands or other organs or tissues such as hemocytes, ganglion, fat bodies etc [49], [51], [52]. Salivary gland dissemination rates obtained from our current study is similar to that observed for a local highly epidemic DENV-2 in the same strain of Ae.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that the proliferation of ZIKV in Ae. aegypti salivary glands is not attributed to direct dissemination from the midgut, but rather a result of viral dissemination and amplification within the glands or other organs or tissues such as hemocytes, ganglion, fat bodies etc [49], [51], [52]. Salivary gland dissemination rates obtained from our current study is similar to that observed for a local highly epidemic DENV-2 in the same strain of Ae.…”
Section: Discussionsupporting
confidence: 80%
“…The alphaviruses VEEV and CHIKV both utilized single amino acid substitutions in the envelope glycoprotein to increase vector competence of Ae. taeniorhyncus [74,75] and Ae. albopictus [8] mosquitoes, respectively.…”
Section: Positive Selectionmentioning
confidence: 99%
“…( Och. ) sollicitans , Psorophora confinnis , Culex (Deinocerites) pseudes , Mansonia indubitans , and M. titillans , among others [5][10]. Many of these mosquitoes thrive near coastal brackish water, can fly long distances from larval sites, prefer to feed on humans or other large mammals, and can tolerate feeding in sunny areas, although they may rest in shaded sites.…”
Section: Introductionmentioning
confidence: 99%